Improving Ready-Made Garment Productivity by Changing Worker Attitude - Islam, Md. Monirul; Adnan, ATM (European Scientific Journal, ESJ, 2016)
Bangladesh is the 2nd largest readymade garment exporter in the world. But in terms of productivity, its performance is below the mark. Many studies were performed to increase the productivity of our readymade garment industry by applying proper line balancing, time study, lean manufacturing system etc. Similarly this paper is an attempt to analyze the potential increase in garment productivity by applying a non-monetary process that is related with changing the behavioral aspect of the readymade garment workers. The study shows only slight change in worker attitude along with proper supervision can bring about a tremendous increase in garment productivity which can make the readymade garment products more price competitive to the foreign buyers.